Dense carbon nanotube films as transparent electrodes in low‐voltage polymer and all‐carbon transistors - Held, Martin; Rother, Marcel; Zaumseil, Jana (Advanced electronic materials, 2018)
Dense but transparent films of long and clean carbon nanotubes grown by the floating catalyst method, transferred and patterned on glass substrates, are employed as source and drain electrodes in top-gate field-effect transistors with both low-mobility semiconducting polymers and high-mobility networks of polymer-sorted semiconducting single-walled carbon nanotubes. Significant enhancement of ambipolar charge injection into the polymer semiconductor compared to gold electrodes is observed, while the limitations of sheet resistance become apparent for the high-mobility nanotube transistors. The injection of charges from gold compared to carbon nanotube electrodes into the semiconducting nanotube network is investigated by means of conductive atomic force microscopy indicating a less defined channel edge for the latter. Metal-free, all-carbon electrolyte-gated transistors with a nanotube network semiconductor as well as nanotube source, drain, and gate electrodes show both hole and electron transport at very low operating voltages.